The Effects of Calcium-Vitamin D and Metformin on Polycystic Ovary Syndrome: A Pilot Study - Batool Rashidi; Fedieh Haghollahi; Mamak Shariat; Farid Zayerii (Elsevier, 2009)
Objective: The aim of this study was to evaluate the effects of calcium-vitamin D and metformin on the menstrual cycle and ovulation in patients with polycystic ovary syndrome (PCOS). Materials and Methods: In this pilot study, 60 infertile PCOS patients were enrolled in a randomized clinical trial and divided into three equal groups. Group 1 received 1,000 mg of calcium and 400 IU of vitamin D per day, orally. Group 2 received the same as Group 1, plus 1,500 mg/day of metformin. Group 3 received 1,500 mg/day of metformin. The patients were treated for 3 months and followed up for a further 3 months. Regularity of menses, number of large follicles (≥ 14 mm) and pregnancy rates were compared among the three groups. Results: Generalized estimating equation tests showed that the number of dominant follicles (≥ 14 mm) during the 2-3 months of follow-up was higher in the calcium-vitamin D plus metformin group than in either of the other two groups (p = 0.03). Conclusion: The effects of metformin and calcium-vitamin D in regulating the menstrual cycle suggest that they could also be effective for the treatment of anovulation and oligomenorrhea, with possible consequences for pregnancy rates in PCOS patients.